Maplirpacept: a CD47 decoy receptor with minimal red blood cell binding and robust anti-tumor efficacy - Mithunah Krishnamoorthy; Mithunah Krishnamoorthy; Ruth Seelige; Christopher R. Brown; Nancy Chau; Natasja Nielsen Viller; Lisa D. S. Johnson; Emma Linderoth; Jean C. Y. Wang; Jean C. Y. Wang; Jean C. Y. Wang; Christopher P. Dillon; et al. (Frontiers in Immunology)
IntroductionCD47 is highly expressed on cancer cells and triggers an anti-phagocytic “don’t eat me” signal when bound by the inhibitory signal regulatory protein α (SIRPα) expressed on macrophages. While CD47 blockade can mitigate tumor growth, many CD47 blockers also bind to red blood cells (RBCs), leading to anemia. Maplirpacept (TTI-622, PF-07901801) is a CD47 blocking fusion protein consisting of a human SIRPα fused to an IgG4 Fc region and designed to limit binding to RBCs.MethodsTo determine maplirpacept binding to RBCs and interference with blood tests, human blood samples were used. The ability of maplirpacept to promote macrophage-mediated phagocytosis of human tumor cells was assessed using both confocal microscopy and flow cytometry. In vivo antitumor efficacy as a monotherapy and in combination with other therapeutic agents was evaluated in xenograft models.ResultsIn the current study, we demonstrate that maplirpacept has limited binding to RBCs while driving enhanced macrophage-mediated phagocytosis of hematological tumor cells in vitro and reducing tumor burden in human xenograft models. Moreover, phagocytosis of neoplastic cells can be enhanced when maplirpacept is combined with other therapeutic agents, including antibodies or chemotherapeutic agents.ConclusionThese preclinical results establish maplirpacept as an effective CD47 blocker that mitigates the potential for anemia in patients.